Valorization of Tropical Biomass Waste by Supercritical Fluid Extraction Technology - Chai, Ho Yee; Suzana, Yusup; Wan Nadiah Amalina, Kadir; Wong, Chung Yiin; Siti Suhailah, Rosli; Muhammad Syafiq Hazwan, Ruslan; Lai, Bridgid Fui Chin; Yiin, Chung Loong (MDPI, 2020)
The inception of sustainable and cleaner extraction technology has paved the way for the innovative development of nonconventional extractions, such as supercritical fluid extraction, apart from conventional extraction counterparts. The concept of biomass waste-to-wealth for the conversion of biomass waste or by-products into value-added products for diversified applications had piqued the prominent interest of researchers and industry players, especially with the abundance of biomass resources readily available in tropical regions that have yet to be tapped into to reach their full potential. In this paper, a critical review of the developments of supercritical fluid technology from its initial inception up to commercialized scalability, including its limitations, extraction of potential tropical biomass wastes for various types of applications, such as biopesticides, bio-repellents, phenolics, and lipids for biofuel, and its role in circular bioeconomy and sustainable development approaches, are discussed in detail.